Temperature chaos is a non-local effect. (1st December 2016) - Fernandez, L A; Marinari, E; Martin-Mayor, V; Parisi, G; Yllanes, D
Abstract: Temperature chaos plays a role in important effects, for example memory and rejuvenation, in spin glasses, colloids, polymers. We numerically investigate temperature chaos in spin glasses, exploiting its recent characterization as a rare-event driven phenomenon. The peculiarities of the transformation from periodic to anti-periodic boundary conditions in spin glasses allow us to conclude that temperature chaos is non-local: no bounded region of the system causes it. We precisely show the statistical relationship between temperature chaos and the free-energy changes upon varying boundary conditions.